Age-related differences in spatiotemporal variables and ground reaction forces during sprinting in boys - Nagahara, R.; Takai,Y.; Haramura, M.; Mizutani, M.; Matsuo, A.; Kanehisa, H.; Fukunaga, T. (Pediatric Exercise Science, 2018)
Purpose: We aimed to elucidate age-related differences in spatiotemporal and ground reaction force variables during sprinting in boys over a broad range of chronological ages. Methods: Ground reaction force signals during 50-m sprinting were recorded in 99 boys aged 6.5-15.4 years. Step-to-step spatiotemporal variables and mean forces were then calculated. Results: There was a slower rate of development in sprinting performance in the age span from 8.8 to 12.1 years compared with younger and older boys. During that age span, mean propulsive force was almost constant, and step frequency for older boys was lower regardless of sprinting phase. During the ages younger than 8.8 years and older than 12.1 years, sprint performance rapidly increased with increasing mean propulsive forces during the middle acceleration and maximal speed phases and during the initial acceleration phase. Conclusion: There was a stage of temporal slower development of sprinting ability from age 8.8 to 12.1 years, being characterized by unchanged propulsive force and decreased step frequency. Moreover, increasing propulsive forces during the middle acceleration and maximal speed phases and during the initial acceleration phase are probably responsible for the rapid development of sprinting ability before and after the period of temporal slower development of sprinting ability.